2014
DOI: 10.1016/j.tjog.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of circulating microRNAs as early markers of preeclampsia

Abstract: Circulating miRNAs deserve further investigation in order to explore their potential role in the pathogenesis of preeclampsia. In particular, miR-1233 might represent a potential marker of early sPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 26 publications
6
108
3
2
Order By: Relevance
“…There was also a higher level of circulating miR-1233 in the group of women who developed PE compared with the group of women with a normal pregnancy. Our results confirmed those of Ura et al (23), who were the first researchers to identify a potential role for miR-1233, which has already been described in renal carcinoma, in predicting PE. It is important to note that both miR-1233 and miR-210, which are upregulated in PE, are also upregulated in renal cell carcinoma.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…There was also a higher level of circulating miR-1233 in the group of women who developed PE compared with the group of women with a normal pregnancy. Our results confirmed those of Ura et al (23), who were the first researchers to identify a potential role for miR-1233, which has already been described in renal carcinoma, in predicting PE. It is important to note that both miR-1233 and miR-210, which are upregulated in PE, are also upregulated in renal cell carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we confirmed the differential expression of several miRNAs that were identified in previous studies (20)(21)(22)(23). Of the 17 miRNAs selected, miR-210-3p, miR-210-5p, miR-1233-3p, and miR-574-5p were upregulated in the sera of women who later developed PE compared with the controls who did not develop PE according to RT-qPCR.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The more unambiguously identified ECFCs, based on well-known endothelial markers and functional properties, may be needed to confirm the levels or roles of circulating ECFCs in the peripheral blood of pregnant women with preeclampsia, because many biomarkers have been used in an attempt to provide a much more effective tool in predicting the risk of occurrence of preeclampsia. 10 …”
mentioning
confidence: 99%